Prevalence and Intensity of Endoparasites in Ribbonfish (Trichiurus lepturus) from (Lamongan) and Tamperan (Pacitan) Fish Landing Sites (TPI) - Himma, Nur Afidatul (Aquatic Life Sciences, 2026)
Parasitic infections in marine fish pose economic and public health risks, particularly when zoonotic species are involved. Ribbonfish (Trichiurus lepturus), a commercially important species in Indonesia, is highly susceptible to endoparasites that may reduce fish quality and threaten human consumers. This study aimed to identify the types, prevalence, and intensity of endoparasites infecting ribbonfish landed at Paciran (Lamongan) and Tamperan (Pacitan). A total of 56 fish samples were examined through necropsy and microscopic observation of internal organs. Two nematode species, Anisakis sp. and Camallanus sp., were detected in the intestine, stomach, and muscle tissues. Prevalence was 0.2% at Paciran and 0.4% at Tamperan, while intensity reached 1.3 and 1.9 ind/individual, respectively. Infected fish were typically larger, with body weights ranging from 100–400 g and lengths of 60–80 cm, and often contained undigested small fish and crustaceans that may serve as intermediate hosts. Although infection levels were classified as low, the detection of zoonotic Anisakis sp. underscores the need for continued monitoring to prevent potential health risks and safeguard fishery resources.